LESSON STUDY UNTUK MENINGKATKAN MUTU PROSES DAN HASIL PEMBELAJARAN PERKULIAHAN DASAR PEMISAHAN ANALITIK - Sumarni, Woro (Universitas Negeri Semarang, 2008)
The research of Lesson Study followed by the observation composed by analyticalÃ‚Â expertise lecturers was conducted. The aims of this activity are to raise the quality of lessonÃ‚Â plan Ã‚Â produced Ã‚Â by Ã‚Â the Ã‚Â lecturers, Ã‚Â the Ã‚Â mastering Ã‚Â of Ã‚Â learning Ã‚Â material Ã‚Â for Ã‚Â each Ã‚Â of Ã‚Â lecturersÃ‚Â conducting Ã‚Â the Principles Ã‚Â of Analytical Separation Ã‚Â course, Ã‚Â the Ã‚Â knowledge Ã‚Â of Ã‚Â observingÃ‚Â the Ã‚Â learning Ã‚Â activity, and motivation Ã‚Â of Ã‚Â lecturer Ã‚Â for Ã‚Â self-developments. The responses ofÃ‚Â lecturers showed that they acquired a good comprehension, particularly on how the studentsÃ‚Â learning and how lecturers teaching. The others are they got a positive value inside theÃ‚Â learning process; they had the ability to improve the learning process systematically throughÃ‚Â collaborative inquiry and they got knowledge from the other lecturers. Thereby, the LessonÃ‚Â Study activity had to be experienced the benefi t by the analytical expertise lecturers. FromÃ‚Â the obtained results, it is suggested that the lesson study would be applied continually andÃ‚Â collaboratively, so we could gain various benefi ts such as collegiality strengthening and theÃ‚Â reinforcement of daily learning activity related to the long term purposes.Keywords: lesson study; process quality; learning result